An investigation of the benefits and barriers of e‐business adoption activities in Yemeni SMEs1. (May 2018) - Abdullah, Ahmed; Thomas, Brychan; Murphy, Lyndon; Plant, Eoin
Abstract : Yemeni small‐ and medium‐sized enterprises (SMEs) are at the early stages of e‐business adoption and their owners and managers need to be supported to gain an understanding of the benefits that their business can achieve from adopting e‐business. Yemeni SMEs are at the early stages of e‐business adoption. The delay in adopting more advanced e‐business solutions are due to factors including the comparatively low level of technology usage within the organization, lack of qualified staff available to develop, implement and support firms' websites, and limited financial resources. A lack of computer software and hardware resources appears to have a detrimental effect on e‐business adoption amongst Yemeni SMEs.